2013
DOI: 10.1182/blood-2013-04-491845
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic actions of statins involve PECAM-1 signaling

Abstract: Key Points• The inhibitory effect of platelet function by statins results, at least in part, in action on PECAM-1.• Statins modulate Lyn activation and PECAM-1 tyrosine phosphorylation, resulting in the inhibition of downstream PI3K-dependent signaling.Statins are widely prescribed cholesterol-lowering drugs that are a first-line treatment of coronary artery disease and atherosclerosis, reducing the incidence of thrombotic events such as myocardial infarction and stroke. Statins have been shown to reduce plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 43 publications
0
20
1
2
Order By: Relevance
“…Statins have antiplatelet effects in vitro, ex vivo, in animal models and in patients293239. Therefore, in order to distinguish their effects on endothelial cells from those on platelets, we used washed platelets from healthy non-medicated volunteers for our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Statins have antiplatelet effects in vitro, ex vivo, in animal models and in patients293239. Therefore, in order to distinguish their effects on endothelial cells from those on platelets, we used washed platelets from healthy non-medicated volunteers for our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Lyn phosphorylates platelet-endothelial cell adhesion molecule 1 (PECAM1, CD31) within its immunoreceptor tyrosine-based inhibitory (ITIM) motif that inhibits platelet activation in response to collagen stimulation 30 . In the presence of the TYMP inhibitor KIN59 we found that inhibition of TYMP activity significantly increased tyrosine phosphorylated PECAM1 (Figure 4C), potentially from Lyn release.…”
Section: Resultsmentioning
confidence: 99%
“…They effectively lower the cholesterol levels, thereby reducing the risk of ischemic heart disease, and stroke. They can also modify endothelial function, control inflammatory response, promote plaque stability, inhibit thrombus formation, reduce platelet aggregation, increase collagen and smooth muscle cells, and maintain a balance between prothrombotic and fibrinolytic mechanisms 5. These are used in the treatment of hyperlipidemia and act on the same pathway of bisphosphonates but on an earlier step.…”
Section: Introductionmentioning
confidence: 99%